Pengembangan Video Pembelajaran Materi Ikatan Kimia Dengan Model ADDIE Sebagai Penunjang Pembelajaran Di Masa Pandemi COVID-19 - Meylin Kawete; Dokri Gumolung; Anderson Aloanis (Chemistry Department, Universitas Negeri Manado, 2022)
The purpose of this study was to develop a Learning Video for Chemical Bonding Materials with the Addie Model as Learning Support during the Covid-19 Pandemic. This research is research and development (Research and Development). This research is a research that refers to the ADDIE model (Analysis, Design, Development or Production, Implementation or Delivery and Evaluations). By following the fifth stage of the ADDIE model, because this is a Video Development research, this research only reaches the fourth stage, namely the Implementation stage. Data collection techniques in this study used a Validation Questionnaire (validation of media experts and validation of material experts) and Student Response Questionnaires. The results of the first material expert validation are included in the